A Peephole into the Brain: Neuropathological Features of Alzheimer’s Disease Revealed by in vivo Two-Photon Imaging - Liebscher, Sabine; Meyer-Luehmann, Melanie (Frontiers in Psychiatry, 2012)
Alzheimer’s disease (AD) is a protein conformational disorder characterized by two major neuropathological features: extracellular accumulations of amyloid-beta peptide in the form of plaques and intracellular tangles, consisting of hyperphosphorylated tau proteins. Several morphological and functional changes are associated with these lesions in the diseased brain, such as dendritic and synaptic alterations, as well as microglial and astroglial recruitment and their activation. The availability of transgenic mouse models that mimic key aspects of the disease and recent advances in two-photon imaging enable the study of fundamental questions in AD pathogenesis and longitudinally monitoring the efficacy of therapeutic intervention. Here, we review the ambitious efforts to understand the relationship between the main neuropathological hallmarks of AD and their associated structural and functional abnormalities by means of in vivo two-photon imaging.